2012
DOI: 10.4172/2155-9600.1000156
|View full text |Cite
|
Sign up to set email alerts
|

Electrophoretic Profiles and Angiotensin I-Converting Enzyme Inhibitory Activities of Nine Varieties of Phaseolus Vulgaris Protein Hydrolysates

Abstract: Nine dry bean (Phaseolus vulgaris) varieties largely grown in Canada were subjected to digestion using trypsin and in vitro gastrointestinal simulation (GIS) followed by a study of their in vitro ACE inhibitor properties and digestibility. GIS hydrolysates of all varieties presented significantly higher ACE inhibitory activities and degree of hydrolysis (DH) compared to those of trypsin hydrolysates (P < 0.05). Cranberry and light red kidney bean protein isolates contained 'T' type phaseolin and had higher DH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Previous researches (Boschin et al, 2014;Mojica et al, 2015;Rui et al 2012aRui et al , 2012b showed the potential of bean proteins to release ACE-inhibitory peptides during hydrolysis catalyzed by bacterial or gastrointestinal enzymes. However, these works focused on the bioactive properties of peptides released from protein isolates from beans and not from whole beans.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous researches (Boschin et al, 2014;Mojica et al, 2015;Rui et al 2012aRui et al , 2012b showed the potential of bean proteins to release ACE-inhibitory peptides during hydrolysis catalyzed by bacterial or gastrointestinal enzymes. However, these works focused on the bioactive properties of peptides released from protein isolates from beans and not from whole beans.…”
Section: Discussionmentioning
confidence: 99%
“…Rui et al (2012a) obtained a degree of hydrolysis of 16% after simulated digestion of pinto bean protein extracts non-thermally treated. They digested nine varieties of beans achieving a degree of hydrolysis between 7 and 16%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The susceptibility of phaseolin, the major storage protein in common bean, is highly variable to proteolysis across different cultivars (Montoya et al, 2008). Rui et al, (2012b) reported that under the same hydrolytic conditions using pepsin/trypsin/α-chymotrypsin subsequently, nine varieties of common bean had significant differences among their DH, being the lowest DH value 7.22% for Dark Red bean, and the highest 16.12% for Pinto beans. Moreover, the DH of common bean protein can be increased with a heat pre-treatment.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Hydrolysis of lentil, pea, bean and chickpea proteins yielded peptides with angiotensin-1 converting enzyme (ACE) inhibitory properties (Vermeirssen et al, 2005;Duranti, 2006; Barbana and Boye, 2010;Boye et al, 2010c;Rui et al, 2012). ACE plays a role in vasoconstriction that results in the elevation of blood pressure (hypertension).…”
Section: Protein Health-benefiting Propertiesmentioning
confidence: 99%